Uji Aktivitas Anti Jamur Ekstrak Etanol Biji Alpukat (Persea americana Mill) Terhadap Jamur Kulit Tricophyton rubrum ATCC 28188, Epidermophyton floccosum ATCC 50266 dan Micospprum canis ATCC 32699) - Masayu Azizah; Panji Taruna Anugrah Akbar; Mauizatul Hasanah (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Antifungal activity test of avocado seed extract (Persea americana Mill) against fungi that cause dermatophytosis skin disease, namely Trichophyton rubrum ATCC 28188, Epidermophyton floccosum ATCC 50266 and Microsporum canis ATCC 32699. Phytochemical test results of avocado seeds contain phenolic compounds, saponins, alkaloids, flavonoids. The antifungal activity test of ethanol extract of avocado seeds used the agar diffusion method, with a concentration of 26,25%, 48,75%, 75%, and the positive control used was ketoconazole and ethanol distillate negative control. The results showed that the diameter of the zone of inhibition against the fungus Trichophyton rubrum ATCC 28188 with an inhibition zone diameter of 7.5 mm, 9.8 mm, 12 mm, against the fungus Epidermophyton floccosum ATCC 50266, the inhibition zone diameter was 7.4 mm, 9, 7 mm, 11.7 mm and against fungi Microsporum canis ATCC 32699 the inhibition zone was 8.4 mm, 10.1 mm, 13.4 mm. It can be concluded that the ethanol extract of avocado seeds has antifungal activity against. Trichophyton rubrum ATCC 28188, Epidermophyton floccosum ATCC 50266 and Microsporum canis ATCC 32699 The greatest antifungal activity was against Microsporum canis at a concentration of 75% with a diameter of 13.4 mm in the strong category